Mastication Influences Human Brain Anatomy - Lucia Lopez-Chaichio; Pablo Galindo-Moreno; Miguel Padial-Molina; Lourdes Gutierrez-Garrido; Roque Rodriguez-Alvarez; Francisco O’Valle; Andres Catena (eJournal of Oral Maxillofacial Research, 2024)
Objectives: The purpose of this observational clinical study was to evaluate the relationship between brain anatomical and volumetric changes in white matter, grey matter, and cerebral cortex thickness with the number of functional occlusal pairs present in the mouth.